The associations between basal salivary cortisol and illness symptomatology in chronic fatigue syndrome - Torres-Harding, Susan (2008)
Hypocortisolism has been reported in chronic fatigue syndrome (CFS), with the significance of this finding to disease etiology unclear. This study examined cortisol levels and their relationships with symptoms in a group of 108 individuals with CFS. CFS symptoms examined included fatigue, pain, sleep difficulties, neurocognitive functioning, and psychiatric status. Alterations in cortisol levels were examined by calculation of mean daily cortisol, while temporal variation in cortisol function was examined by means of a regression slope. Additionally, deviation from expected cortisol diurnal pattern was determined via clinical judgment. Results indicated that fatigue and pain were associated with salivary cortisol levels. In particular, variance from the expected pattern of cortisol was associated with increased levels of fatigue. The implications of these findings are discussed.